Classification of Some Social and Psychological Factors Affecting Drug Addiction Using the Characteristic Analysis - Sarah Ismael Khalel,Dr. Ammar Kuti Nasser,Nihad Sharif (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Distinguished analysis was used to classify some factors affecting drug addiction into several groups depending on variables with discriminatory characteristics. The study includes drawing a random sample for each group separately. Using the linear characteristic function and then classifying some of the factors affecting drug addiction on the basis of a set of accompanying variables, despite the lack of studies in this field, but it presents some influences on social and psychological factors It also appeared in the distinctive multivariate application method to distinguish the social and psychological factors that contribute significantly to disparity. It was found that the variable X6 (escape from problems and frustration) X10 (teaching to say no to wrong things) contributed significantly to distinguishing between social and psychological factors affecting drug addiction .